2014
DOI: 10.1002/bjs.9645
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcome of malignant colonic obstruction in the Dutch Stent-In 2 trial

Abstract: ISRCTN46462267 ( http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
160
7
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(175 citation statements)
references
References 23 publications
4
160
7
4
Order By: Relevance
“…While colonic self-expanding metallic stents may offer an effective treatment option in patients with OCRC, however, it has also been reported that stent placement for OCRC was associated with the risk of recurrence. 21 Therefore, the efficacy of colonic self-expanding metallic stents remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…While colonic self-expanding metallic stents may offer an effective treatment option in patients with OCRC, however, it has also been reported that stent placement for OCRC was associated with the risk of recurrence. 21 Therefore, the efficacy of colonic self-expanding metallic stents remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…12,46,48 Sloothaak et al 12 reanalyzed the largest data set (from the Stent-In-2 trial in 2014). They excluded the benign cases and those with advanced disease (palliative).…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
“…Cumulative incidence of overall disease recurrence was 26% in the surgery group, 34% in the unperforated SEMS group and 83% in the perforated SEMS group (P < 0.01). 12 The concern therefore is that short-term gains would be negated by poorer long-term outcomes. If true, this would be an inappropriate trade off in patients fit enough to undergo surgery in whom the intent is curative.…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Malgras showed an increased metastatic process and shorter survival time in a mouse model of colonic cancer treated with SEMS [14] . Besides in the last decade many studies have been published, including randomized controlled trials (RCTs) and systematic reviews, with conflicting results comparing SEMS as BTS and emergency surgery in terms of safety, morbidity, disease free survival (DFS), recurrence rate and overall survival (OS) [15][16][17][18][19][20] . Actually surgeons are not allowed to consider CS as BTS for young and potentially curable patients.…”
Section: Introductionmentioning
confidence: 99%